Opportunities of Internationalization of French Small and Medium Enterprises in Russia and Central/Eastern Europe - Charrier, Ines; Štěrbová, Ludmila, 1957-; Mercier Suissa, Catherine; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2010)
Only one third of the French SMEs are going abroad. However, this option can be an opportunity for the enterprises to extend their growth. The Chinese market is often designated to be the best place to invest. Nevertheless, it is far from France geographically and culturally. Russia and Central/Eastern Europe represent for French SMEs huge and frequently unknown markets, closed to France with all the benefice of their accession to the European Union. These regions have economic and demographic potentials because of their singular history. The study of these countries will show the possible market development in which the French companies and specially SMEs have competences and know-how highly valuable in these markets. Furthermore, the European and French incentives for SMEs and the support of different organizations are additional assets to facilitate the internationalization.
Vedoucí práce: Ludmila Štěrbová
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: international Business - Central European Business Realities [obor dipl. práce]; diplomové práce; master's theses